Working Memory Load and Reminder Effect on Event-Based Prospective Memory of High- and Low-Achieving Students in Math. (September 2017) - Chen, Youzhen; Lian, Rong; Yang, Lixian; Liu, Jianrong; Meng, Yingfang
The effects of working memory (WM) demand and reminders on an event-based prospective memory (PM) task were compared between students with low and high achievement in math. WM load (1- and 2-back tasks) was manipulated as a within-subject factor and reminder (with or without reminder) as a between-subject factor. Results showed that high-achieving students outperformed low-achieving students on all PM and n -back tasks. Use of a reminder improved PM performance and thus reduced prospective interference; the performance of ongoing tasks also improved for all students. Both PM and n -back performances in low WM load were better than in high WM load. High WM load had more influence on low-achieving students than on high-achieving students. Results suggest that low-achieving students in math were weak at PM and influenced more by high WM load. Thus, it is important to train these students to set up an obvious reminder for their PM and improve their WM.